Annual Plan 1968-69 Haryana State Part II-Statement - Planning Commission (Planning Commission, 1968)
Consolidated Statement (for sub-heads of development) Financial outlay, Centrally sponsored schemes Break-up of financial outlay, Main Physical targets Detailed statement (for schemes under various sub-heads of development), Agricultural Production Agricultural Department Agricultural Production Agricultural University Minor Irrigation Agriculture Department Minor Irrigation Irrigation Department Consolidation of Holdings Animal Husbandry Dairying and Milk Supply, Forests Soil Conservation Agriculture Department.
Planning Department, Haryana